Elements of Northern Sotho orthography : a linguistic approach - Malepe, Maria Kgabo (My University, 2006)
Refer to the document
Thesis (M.A. (African Languages)) -- University of Limpopo, 2006
Keywords: Orthography; Spelling; Northern Sotho language; Northern Sotho language -- Orthography and spelling